2010
DOI: 10.3109/10837450903246416
|View full text |Cite
|
Sign up to set email alerts
|

Use of xanthan and its binary blends with synthetic polymers to design controlled release formulations of buccoadhesive nystatin tablets

Abstract: Various buccoadhesive nystatin tablets formulations containing xanthan, carbopols (934P, 971P, 974P), PVP K30 or PEG 6000 or their binary blends were prepared. The powders were compressed into tablets at a constant compression pressure. Drug release behaviour, swelling and erosion indices and strength of bioadhesion in vitro to a biological membrane were investigated. The interaction between nystatin and polymers was investigated by DSC and FT-IR. Tablets containing the different types of carbopol alone consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…11). The figure shows that the original nystatin showed a few small peaks, ones that started to appear above 100 o C. As nystatin does not melt, these peaks could be due to a gradual decomposition of nystatin as has been reported previously (Sakeer et al 2010). Lactose showed two endothermic peaks at 148 and 219 o C. The first endothermic peak corresponds to the dehydration of crystallization water; the second endothermic peak coincides with the melting of a lactose monohydrate.…”
Section: Ft-ir and Xrd Studiesmentioning
confidence: 74%
“…11). The figure shows that the original nystatin showed a few small peaks, ones that started to appear above 100 o C. As nystatin does not melt, these peaks could be due to a gradual decomposition of nystatin as has been reported previously (Sakeer et al 2010). Lactose showed two endothermic peaks at 148 and 219 o C. The first endothermic peak corresponds to the dehydration of crystallization water; the second endothermic peak coincides with the melting of a lactose monohydrate.…”
Section: Ft-ir and Xrd Studiesmentioning
confidence: 74%
“…Previous studies revealed important economical and pharmaceutical advantages of xanthan gum over other polymers [20]. The natural gum possess properties of reduced burst initial release as well as more reproducible and predictable drug release possibly following zero order kinetics [21].…”
Section: Introductionmentioning
confidence: 99%